(untitled) (Veterinary Science, 2023)
The objective of this work is to report the presence of Werneckiella equi, in a horse from the city of Salta in order to provide information of regional epidemiological relevance and also document the first case of infestation by this parasite in the Northwest of Argentina. A horse of about 8 years old with intense itching and poor body condition, that lived on a property in the urban area of the city of Salta, Argentina, was brought to the consultation. In the particular inspection of the skin, lice were observed, which were collected and sent to the laboratory. Based on the clinical information, further analysis was performed. On the basis of clinical information and parasitological studies, it was determined that the animal was suffering from an infestation of Werneckiella equi. The horse was treated with oral ivermectin, showing improvement and disappearance of the parasites on the skin. What is described in this work is the first report at a regional level and highlights the possibility of occurrence of this presentation in horses that show symptoms of pruritus